Protein cage nanostructure as drug delivery system: magnifying glass on apoferritin. (3rd July 2017) - Belletti, Daniela; Pederzoli, Francesca; Forni, Flavio; Vandelli, Maria Angela; Tosi, Giovanni; Ruozi, Barbara
ABSTRACT: Introduction : New frontiers in nanomedicine are moving towards the research of new biomaterials. Apoferritin (APO), is a uniform regular self-assemblies nano-sized protein with excellent biocompatibility and a unique structure that affords it the ability to stabilize small active molecules in its inner core. Areas covered : APO can be loaded by applying a passive process (mainly used for ions and metals) or by a unique formulative approach based on disassemby/reassembly process. In this article, we aim to organize the experimental evidence provided by a number of studies on the loading, release and targeting. Attention is initially focused on the most investigated antineoplastic drug and contrast agents up to the most recent application in gene therapy. Expert opinion : Various preclinical studies have demonstrated that APO improved the potency and selectivity of some chemotherapeutics. However, in order to translate the use of APO into therapy, some issues must be solved, especially regarding the reproducibility of the loading protocol used, the optimization of nanocarrier characterization, detailed understanding of the final structure of loaded APO, and the real mechanism and timing of drug release.